2022
DOI: 10.1371/journal.pone.0268863
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bacterial contamination and the effectiveness of UV light-based reprocessing of everyday medical devices

Abstract: Background The reprocessing of daily used medical devices is often inadequate, making them a potential source of infection. In addition, there are usually no consistent and technically standardized procedures available for this purpose. Hence, the aim of this study is to analyze the bacterial contamination and the effectiveness of Ultraviolet light-based (UV light-based) reprocessing of daily used medical devices. Material and methods Six different everyday medical devices (20 each; stethoscopes, tourniquets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…The results included one article in the "critical," 2 in the "high," three in the "moderate," and seven in the "low" category. The "critical" classification for the risk of bias assessment in the study of Rudhart et al (2022) was due to the sample that was too varied with an unequal number per type of sample, even though all of them were classified as semi-critical medical devices. In addition, there was no single standard for each contamination and control group to compare interventions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results included one article in the "critical," 2 in the "high," three in the "moderate," and seven in the "low" category. The "critical" classification for the risk of bias assessment in the study of Rudhart et al (2022) was due to the sample that was too varied with an unequal number per type of sample, even though all of them were classified as semi-critical medical devices. In addition, there was no single standard for each contamination and control group to compare interventions.…”
Section: Resultsmentioning
confidence: 99%
“…The disinfection process simply uses low-level disinfectants (26). Rudhart et al, (2022) and Sebastian Marcos et al, (2020) results showed that the reduction of bacteria in non-critical devices ranges from 67.9% to sterile (100% bacteria-free) after UV-C exposure. Pre-cleaning using water wipes can be applied to apparently dirty or non-critical objects with surfaces that tend to be uneven, thereby allowing a lot of dirt to be tucked in.…”
Section: Discussionmentioning
confidence: 99%
“…They were then sprayed with 70% molecular grade ethanol to decontaminate their surfaces and left to air-dry, then placed into open sterile plastic petri dishes. The coupons in the petri dishes were then irradiated on each side for 5 min using the sterilizing UV light within the BSC for a more thorough surface decontamination step ( Rudhart et al, 2022 ; Rutala et al, 2023 ). Post UV-irradiation, lids were placed on the petri dishes, which were then labelled and stored for experimental runs.…”
Section: Methodsmentioning
confidence: 99%
“…To prevent the transmission of pathogens via displays, there would have to be fast automatic disinfection between two users. In theory, it is possible to reduce bacteria on surfaces within seconds by using strong UVC radiation sources (UVC: ultraviolet radiation between 100 and 280 nm) such as mercury vapor lamps, as has already been proven by Rudhart et al (2022), Petersson et al (2015), Moore et al (2012) [5][6][7] and others. Unfortunately, UVC radiation could also harm humans in case of an accidental irradiation [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 96%